Neonatal intensive care: outcomes and long-term developmental implications for preterm infants - Sharma, Saurabh; Kumar Sahu, Mahendra (Journal of Neonatal Surgery, 2025)
Neonatal Intensive Care Units (NICUs) offer preterm infants’ life-saving medical interventions to help them survive complications related to prematurity. Preterm infants still face major obstacles in terms of long-term developmental outcomes, even though the immediate results of NICU care, such as survival rates and the avoidance of acute morbidity, have improved over time. This abstract explores the intricate connection between NICU care and preterm infants' long-term development and health, with a particular emphasis on cognitive, motor, and social-emotional outcomes. According to studies, preterm babies especially those born at extremely low birth weights—are more likely to experience behavioral issues, learning disabilities, and neurodevelopmental delays as they get older. However, improvements in NICU procedures, including better nutritional interventions, developmental care, and respiratory support, have improved overall prognosis. Long-term developmental obstacles still exist despite these advancements, calling for constant observation and early intervention techniques. This article examines current studies on the results of preterm infants treated in the intensive care unit (NICU), focusing on the long-term health consequences and the significance of early therapeutic interventions in reducing developmental risks. To improve the quality of life and developmental paths of preterm infants, it emphasizes the necessity of ongoing innovation in neonatal care as well as extensive follow-up services.